Microbial And Proximate Properties Of Lime Juice Bio-Preserved Ogi Procured From New Benin Market, Benin City, Edo State, Nigeria - C. A. Ngwoke; F. A. Igiebor (Journal of Applied Sciences and Environmental Management)
Ogi, made from maize cereal is widely used in West Africa, especially as a weaning diet for children and could be preserved inwith the water decanted after every 24hours or in the freezer. However, these preservative methods are labour intensive or expensive. Hence, the objective of this paper is to evaluate the microbial and proximate properties of lime juice bio-preserved Ogi procured from New Benin Market, Benin City, Edo State, Nigeria using appropriate standard techniques and procedures. Bacteria isolates from both the control and test samples were characterized by cultural methods in appropriate media and identified based on their morphological and biochemical characteristics. Proximate analysis of the samples stored with lime juice and that of the control, stored with water was also carried out. The total bacteria count for samples stored at room temperature (28±2oC) ranged from 2 x 103 to 33.3 x 103CFU/g, while the fungal count was between 12 x 103 to 29 x 103 CFU/g. Organisms identified from the control sample were Lactobacillus sp, Lueconostocs sp and Staphylococcus aureus. The experimental samples yielded Corynebacterium sp, Flavobacterium sp and Klebsiella sp. The presence of lime inhibited the growth of some organisms but did not affect the variety of microorganisms present. Determination of the proximate analysis of the samples stored with lime juice and that of the control, stored with water showed no significant difference in the composition of the nutrients. However, the samples treated with lime juice had a longer shelf life and better organoleptics.